Negara Kesatuan Republik Indonesia (NKRI) Dalam Tinjauan Maqasid Syariah - Dharma Setyawan; Mu'adil Faizin (Nizham Jurnal Studi Keislaman, 2018)
Discussions about the government in Islam, and the relationship between the state and the religion has always not ended. Bringing up the wealth of Muslim’s ijtihad in examining the intellectual basis of the role of the state and the government in an Islamic way. Peolemics are finally more visible as a matter of ijtihadiyah. Often, the question arises about the content of Islamic philosophical values ​​in the formation of NKRI. Therefore, this article is researching the construction of NKRI in the view of Maqasid Syariah. This study uses the theory of Maqasid Syariah is examining the deepest intention of the establishment of the Unitary Republic of Indonesia (NKRI) and its components in it, about Pancasila, Pancasila Democracy, Constitution (UUD) 1945 and The Presidential Governance System. This study proposes that Pancasila contained a solemnity that prioritized religious maintenance, further integrating it to other al-kulliyat al-khamsah. Furthermore, Pancasila Democracy is present as the uniform of the political street of democracy. The Constitution (UUD) 1945 is a constitution that oriented to Maqasid Shariah in the form of Human Rights to address the pluralism of the ummah. Associated with the Presidential Government System is a mutaghayirat ijtihad. Finnaly, the Unitary State of the Republic of Indonesia (NKRI) was formed on the basis of ijtihadiyah which is considered to be beneficial and refuse mudharat for Indonesia Keywords: NKRI, Maqasid Syariah, Mutaghayirat, Ijtihadiyah.